Pioneering an Autonomous Village Through the Management of Sustainable Tourism Village Based on Local Potential in Malang Regency - Winarno, A; Wijijayanti, T; Agustina, Y; ., Sopingi (KnE Social Sciences, 2018)
Malang Regency is one of the regencies in Indonesia which is located on East Java and also the second widest regency among cities and regencies in East Java. It has really good potential to be turned into an autonomous economic and energy village. This study aims to analyze and map based on its region potentials through an idea of building a tourism village based on sustainable local potential. The region which will be the limelight is Sumberagung and Pait villages, Northern Malang. The analysis was done using descriptive study and also the SWOT approach. The result shows that there are big potentials of the productive economy which can be developed sustainably, by developing eco-tourism and socio-cultural community support. Alternative energy can also be potentially developed, such as utilization of waste cattle dairy, and solar energy. The community empowerment through the university-controlled village is also needed sustainably and constantly with the village programs. Keywords: economically autonomous village, Self-powered energy village, sustainably managed village